Another face of dermal fillers - Witmanowski, Henryk; Błochowiak, Katarzyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Potential complications related to dermal fillers depend on the type of the fillers and the site of their application. The classification of dermal filler complications can be divided into early and late, and into minor and major events. According to their mechanism, they can be divided into non-ischaemic and ischaemic complications. The aim of this study is to present possible complications related to dermal fillers, to explain their aetiology and to propose preventive management and treatment. Non-ischaemic complications can be technique-dependent and include the reactions at the site of the injection, contour irregularities, and inflammatory and infectious reactions. They are usually resolved as a matter of course after 2–7 days. Arterial or venous occlusion leads to ischemia, with subsequent necrosis of the skin and/or vision loss.